Race and policing. A study of police custody - Britton, Nadia Joanne (The British journal of criminology, 2000)
Examines the meaning of race in the police custody process in Great Britain. Failure of a convenient 'race relations' initiative of senior officers; Important questions about the potential value of independent civilian representation in police custody